Optimizing BOPPPS Teaching Strategy in Influencing College Students after Class Sports Activities - Zhang, Hua (International Journal of Social Sciences and Public Administration, 2024)
Lifelong sports aim to deeply embed the concept into people’s daily lives. This study extends physical education beyond the classroom with innovative teaching models to boost students’ extracurricular sports participation and develop lifelong physical education skills. It aimed to optimize college students’ sports participation and explore effective teaching models and strategies. The study involved 364 students from basketball, volleyball, and aerobics majors at Xinyang Normal University, using a descriptivecomparative-correlational research design and a self- constructed questionnaire. The study employed statistical tools such as ranking, standard deviation, weighted mean computation, frequency count and percentage, T-test, and Spearman’s rho Correlation Coefficient for a methodical presentation, analysis, and interpretation of data. It concluded that all components of the BOPPPS model-Bridge in, Objective, Preassessment, Cognitive Participation, Participant Learning and Behavioral Participation, Post-assessment and learning outcomes, and Emotional Participation-are effective in engaging students in PE classes. The analysis showed insignificant differences based on respondents’ sex, age, and elective choices, thus accepting the null hypothesis. However, the study found a significant relationship between the four elements of BOPPPS (Bridge in, Objectives, Pre-assessment and cognitive engagement, Participation Learning and Behavioral Participation, Post-assessment and effect Participation, and Emotional Participation) and respondents’ participation in after class sports activities, including interests and motivation, habits and plans, and attitude and behavior, necessitating the rejection of the null hypothesis. It is recommended to continue promoting inclusivity and diversity in sports participation to ensure equitable access and opportunities for all individuals, regardless of demographic characteristics. Emphasizing and integrating the BOPPPS framework into sports education programs can enhance participants’ interest, motivation, habits, plans, attitudes, behaviors, and overall engagement in after class sports activities, leading to more effective outcomes.